Leaf area and intermittent misting on hop plants propagation by stem cuttings - Gomes, Erik Nunes; Machado, Marília Pereira; Miola, José; Deschamps, Cícero (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 508-513).